Integration of Artificial Intelligence in Education Management Systems to Improve the Quality of Islamic Education - Anshori, Irfan; Yansyah, Dedy; Nasiroh, Nasiroh; Urfi, Urfi; Ismail, Hajah Amirah Binti Haji (Thawalib: Jurnal Kependidikan Islam, 2025)
The need for manual school management is a crucial problem in the national education system. This will have a profound impact on the ongoing learning process. This study aims to analyse the progress of information and communication technology in the form of artificial intelligence applied in managing school administration to produce an innovative quality of education and management of Islamic education. The type of this research is qualitative phenomenology, using a descriptive approach. The study subjects included principals, teachers, education personnel, and students. Data collection techniques include interviews, observations, and documentation.. Data validity techniques include confirmability tests, with administrative staff as confirmation. The results of this study illustrate that advances in information and communication technology can facilitate the completion of school management administration, from increasingly automated administrative mechanisms, financial management, activity planning, monitoring, and evaluation of learning to personalisation of learning. In Islamic education, artificial intelligence can help create innovative and high-value education, with an adaptive Islamic religious education learning system, abundant learning methods, an Islamic education analysis curriculum, and the ability to access digital learning resources. This research has the potential to develop further, along with the increasingly rapid development of artificial intelligence, especially the development of artificial intelligence in aspects of Islamic education, which can be studied in cultural and religious values.